Animal source foods for nutrition impact: Evidence and good practices for informed project design - International Livestock Research Institute; Land O'Lakes (International Livestock Research Institute, 2017)
This is a recording of a Land O’Lakes/ILRI Animal Source Foods for Nutrition Impact workshop, Nairobi, 4 May 2017